Analyzing Workload and Turnover Intention through Work Stress: Strengthening Retention Strategies from an Educational Perspective - Farhana, Nur Fitria; Hartati, Wiwi; Risdianto, Risdianto (CV. Tripe Konsultan, 2025)
This study aimed to analyze the influence of workload on turnover intention with work stress as a mediating variable among employees of CV Semar Berkah Mandiri. A quantitative research approach was employed, involving 43 respondents selected through a saturated sampling technique. Data were collected using a structured questionnaire and analyzed using multiple linear regression, coefficient of determination (R²), t-tests, F-tests, and Sobel tests with the assistance of IBM SPSS 25. The results reveal that workload has a positive and significant impact on turnover intention. Moreover, workload also positively affects work stress, which, in turn, significantly increases turnover intention. Mediation analysis demonstrates that work stress plays a crucial mediating role in the relationship between workload and turnover intention. From an educational perspective, this study emphasizes the importance of employee development programs in mitigating the negative effects of workload and stress. Continuous training and organizational learning initiatives can strengthen employees’ resilience, adaptability, and problem-solving skills, thereby reducing turnover intention. Companies are encouraged to integrate educational initiatives into their human resource management strategies as part of a holistic approach to workload management and employee retention.